2016
DOI: 10.1111/nan.12332
|View full text |Cite
|
Sign up to set email alerts
|

Non‐motor involvement in amyotrophic lateral sclerosis: new insight from nerve and vessel analysis in skin biopsy

Abstract: We demonstrated a cutaneous sensory and autonomic denervation in ALS and a previously undescribed relationship between autonomic and vascular involvement that appeared to be linked to the disease progression rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…IENFD has been reported to be reduced also in other painful conditions, such as Guillain‐Barré syndrome, meralgia paraesthestica, notalgia, Ehlers‐Danlos syndrome, and fibromyalgia and non‐painful disorders, such as Parkinson disease and related disorders, amyotrophic lateral sclerosis, critical illness, and peripheral arterial disease …”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…IENFD has been reported to be reduced also in other painful conditions, such as Guillain‐Barré syndrome, meralgia paraesthestica, notalgia, Ehlers‐Danlos syndrome, and fibromyalgia and non‐painful disorders, such as Parkinson disease and related disorders, amyotrophic lateral sclerosis, critical illness, and peripheral arterial disease …”
Section: Epidemiologymentioning
confidence: 99%
“…• Expansion in knowledge on the pathophysiology of SFN will inform the development of new therapies. amyotrophic lateral sclerosis, [44][45][46] critical illness, 47 and peripheral arterial disease. 48 New techniques to determine the IENFD with indirect immunofluorescence, 49 automated PGP9.5 immunofluorescence staining (laboratory developed test), 50 and 3D analysis 51 have been reported.…”
Section: Skin Biopsymentioning
confidence: 99%
“…Similarly, further studies have demonstrated that up to 75% of patients with ALS have small-fibre pathology, evident as a decreased density of IENFs 148 , and exhibit asymptomatic involvement of autonomic nerves and Meissner corpuscles 147 . One study suggested that loss of IENFs was only seen in patients with spinal-onset ALS 149 , but a larger study that included patients with sporadic and genetic ALS found no correlations between phenotype, genotype and disease course 148 .…”
Section: Stromamentioning
confidence: 99%
“…Beyond classic SFNs, skin biopsy can be used to identify small-fibre pathology in painless neuro degenerative disorders, such as Parkinson disease (PD) 144,145 and amyotrophic lateral sclerosis (ALS) [146][147][148] . Evidence shows that patients with PD exhibit a marked loss of IENFs and Meissner corpuscles that accompanies abnormal tactile, thermal and mechanical pain perception 144 .…”
Section: Stromamentioning
confidence: 99%
“…In this issue of Neuropathology and Applied Neurobiology, Nolano and colleagues reported significant cutaneous sensory and autonomic denervation in a cohort of sporadic ALS patients, including primary lateral sclerosis (PLS), and associate these changes to a faster rate of disease progression. Specifically, nonlength‐dependent loss of intraepidermal nerve fibres along with reduced density of Meissner corpuscles and cholinergic/noradrenergic pilomotor nerve fibres was reported in both the typical ALS phenotype and PLS.…”
mentioning
confidence: 99%